2018
DOI: 10.1038/s41598-018-35144-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prognostic Accuracy of the quick Sepsis-Related Organ Failure Assessment between Short- & Long-term Mortality in Patients Presenting Outside of the Intensive Care Unit – A Systematic Review & Meta-analysis

Abstract: The purpose of this meta-analysis was to compare the ability of the qSOFA in predicting short- (≤30 days or in-hospital mortality) and long-term (>30 days) mortality among patients outside the intensive care unit setting. Studies reporting on the qSOFA and mortality were searched using MEDLINE and SCOPUS. Studies were included if they involved patients presenting to the ED with suspected infection and usage of qSOFA score for mortality prognostication. Data on qSOFA scores and mortality rates were extracted fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 65 publications
1
8
0
3
Order By: Relevance
“…The Sequential Organ Failure Assessment (SOFA) score, used to codify the degree of organ dysfunction, is a simple and effective method to monitor patient condition and disease progression, and is widely used in ICUs to evaluate the severity and prognosis of patients with sepsis (Ferreira et al, 2001;Tan et al, 2018;Lambden et al, 2019). SOFA score is a total score including six domains: respiratory system (PaO 2 /FiO 2 ), renal system (creatinine), central nervous system (Glasgow Coma Score), coagulation system (platelet counts), hepatic (bilirubin), and cardiovascular system (systolic blood pressure).…”
Section: Introductionmentioning
confidence: 99%
“…The Sequential Organ Failure Assessment (SOFA) score, used to codify the degree of organ dysfunction, is a simple and effective method to monitor patient condition and disease progression, and is widely used in ICUs to evaluate the severity and prognosis of patients with sepsis (Ferreira et al, 2001;Tan et al, 2018;Lambden et al, 2019). SOFA score is a total score including six domains: respiratory system (PaO 2 /FiO 2 ), renal system (creatinine), central nervous system (Glasgow Coma Score), coagulation system (platelet counts), hepatic (bilirubin), and cardiovascular system (systolic blood pressure).…”
Section: Introductionmentioning
confidence: 99%
“…The qSOFA scores can be used outside of the intensive care unit (ICU) for predicting mortality or ICU stay [4][5][6][7][8][9]. However, several meta-analyses of qSOFA scores have shown that these scores had a poor sensitivity for predicting in-hospital mortality [10][11][12][13][14]. Early warning scores [15,16], a tool for identifying hospitalized patients at risk of deterioration, have been proposed for predicting hospital mortality in those with suspected sepsis in the ED [7,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It appears that the qSOFA score may have low sensitivity but high specificity as a prognosticator of mortality. [5][6][7][8][9][10][11][12] Age, sex and HIV status have been shown to independently predict mortality in patients with infection in the US and have been used in prior qSOFA validation studies in resource-limited settings. [13] There is limited research on the prognostic value of qSOFA in resourcelimited settings -initial results from developing countries [13] and African countries are encouraging.…”
mentioning
confidence: 99%